Synthesis and Characterization of Cobalt(II) , Nickel(II) and Copper(II) with [2-(4-Isobutyl-phenyl)-propionic acid N'-{(4-isobutyl-phenyl)-propionyl}-hydrazide] - Ayad S. Hameed; Modher Y. Mohammed; Adnan A. Hamada (Tikrit Journal of Pure Science, 2023)
Synthesis of complexes of Cobalt(II), Nickel(II) and Copper(II) with the ligand [(2-(4-Isobutyl-phenyl)-propionic acid N'-{(4-isobutyl-phenyl)-propionyl}-hydrazide]  (LH) have been prepared and characterized by, atomic absorption spectrophotometer (AAS), Infrared spectra, electronic spectra, molar conductivity measurements and magnetic moment measurements; It has been found that the ligand behaves as a neutral bidentate, Ligand forming chelates with 1:2 (metal: ligand), octahedral structure is suggested in Co(II) and Ni(II) complexes and square planer in Cu(II) complexes according to the analytical results